VStore: Feasibility and acceptability of a novel virtual reality functional cognition task - Porffy, Lilla A.; Mehta, Mitul A.; Mouchlianitis, Elias; Shergill, Sukhi S. (Frontiers in Virtual Reality, 2022)
Virtual reality (VR) is becoming an increasingly popular tool in neuroscience and mental health research. In recent years, efforts have been made to virtualise neuropsychological testing with the intent to increase the ecological validity of cognitive assessments. However, there are some limitations in the current literature – feasibility and acceptability data are often not reported or available and sample sizes have generally been small. In this study, we describe the development and establish the feasibility and acceptability of use of a novel functional cognition VR shopping task, VStore, in three separate samples with data from a total of 210 participants. Two samples include healthy volunteers between the ages of 20 and 79 and there is one clinical cohort of patients with psychosis. Main VStore outcomes were: 1) verbal recall of 12 grocery items, 2) time to collect items, 3) time to select items on a self-checkout machine, 4) time to make the payment, 5) time to order hot drink, and 6) total time. Feasibility and acceptability were assessed by the completion rate across the three studies. VR induced adverse effects were assessed pre- and post-VStore administration to establish tolerability. Finally, as an exploratory objective, VStore’s ability to differentiate between younger and older age groups, and between patients and matched healthy controls was examined as preliminary indication of its potential utility. The overall completion rate across the studies was exceptionally high (99.95%), and VStore did not induce any adverse effects. Additionally, there was a clear difference in VStore performance metrics between both the patients and controls and between younger and older age groups, suggesting potential clinical utility of this VR assessment. These findings demonstrate that VStore is a promising neuropsychological tool that is well-tolerated and feasible to administer to both healthy and clinical populations. We discuss the implications for future research involving neuropsychological testing based on our experience and the contemporary literature.